Arabian studies - Serjeant, R. B.; Bidwell, Robin Leonard (University of Cambridge oriental publications ;, 2005)
The articles in this volume cover a wide variety of themes, mainly in the fields of history and social anthropology, with one paper on a literary topic, making this a book of multi-disciplinary interest for those specialising in the study of the Arabian peninsula.